Marketing Strategy Using SWOT Analysis in Increasing Sale Nasi Kuning Mak’im in Selangor Malaysia - Alfarisi, Abdul Rozaq; Musarofah, Siti; Sulton, Muhammad (PT Agung Media Publisher, 2025)
Nasi Kuning Mak’Im is a culinary business founded in Malaysia in 2016, specializing in Indonesian cuisine using high-quality ingredients at affordable prices. However, increasing competition from similar businesses poses a challenge to sustaining and growing the enterprise. Developing an effective marketing strategy is crucial to addressing these challenges and ensuring business growth. This study aims to evaluate the marketing strategies of Nasi Kuning Mak’Im using SWOT analysis to enhance sales performance. The research employs a descriptive qualitative approach conducted at the Nasi Kuning Mak’Im SME in Selangor, Malaysia. Data were collected through direct interviews with key stakeholders, field observations, and literature review. Key informants included the business owner and loyal customers, providing insights into both operational and customer perspectives. The findings from the SWOT analysis and the internal-external matrix indicate that the most appropriate strategy for Nasi Kuning Mak’Im is the Strengths-Opportunities (S-O) strategy. This approach leverages the business's strengths, such as product quality and affordability, to capitalize on market opportunities and build competitiveness while fostering customer loyalty. The application of the S-O strategy demonstrates that by aligning internal strengths with external opportunities, Nasi Kuning Mak’Im can enhance its market position and maintain sustainable operations amid a competitive landscape. Recommendations for further implementation of the strategy are provided to support long-term growth and customer retention.